Demand Response Program for Office Energy Management - Vichanpol, Bunyawat; Khonrang, Jarun (International Journal of English Literature and Social Sciences (IJELS), 2019)
Abstract: The study on Demand Response Program for Office Energy Management aims to design the demand response program being used with a solar energy generating set for office energy management .The experimental data are collected from the whole electrical power consumption in the office from 6 a.m. – 6 p.m. in order to seek for the guideline for the office energy management for the reduction at the demand peak through a demand response program and the guideline for the co-using with the alternative energy in reducing the peak demand. The electric appliances used in the office can be classified into two groups; unable stop and able stop at for some time. This study emphasizes on the later. From the experimental result, it discovered that the DR Program used with an electric generating set from solar cell can reduce the electricity consumption at 70.18 % of all energy used in the office meanwhile in 10 minutes the reduction capacity is 74.63 % and in 15 minutes the reduction rate of energy consumption is 80.28 %.